Lactic Acid Bacteria R & D for Food, Health and Livestock Purposes - Kongo, Marcelino (IntechOpen, 2013)
Ongoing scientific research in many parts of the world on the genomics, proteomics and genetic engineering of LAB is increasing our understanding of their physiology, pushing further the boundaries for their potential applications. "Lactic Acid Bacteria - R&D for Food, Health & Livestock Purposes" is a compilation and discussion of the outstanding scientific research activities concerning actually and future applications of LAB. It is directed to a vast public of readers - researcher, academics, corporate R&D, students or just curious interested in the subject.